Transformarse en "llaves del bien": mujeres musulmanas, saberes y praxis en la ciudad de Buenos Aires = Becoming ‘keys to virtue’ : muslim women, knowledge and praxis in Buenos Aires - Valcarcel, Mayra S. (Ciencias sociales y religión, 2019)
This article sets out to describe women’s religious classes taught in a mosque in the city of Buenos Aires between 2014 and 2015. We first outline the principles and ethical-religious values transmitted in them. We then go on to analyze the dynamics and characteristics that configure this space of learning and socialization. We inquire into the relationship between knowledge and "good behavior" (adab), paying special attention to the meanings built around ethical principles in Islam, personal experience and the practice of worship. We conclude with some thoughts about the anthropologist’s involvement during the fieldwork and the fruitful challenges that arise between religious studies and gender studies.